Infantile chronic idiopathic intestinal pseudo-obstruction: the role of small intestinal manometry as a diagnostic tool and prognostic indicator - Fell, J M; Smith, V V; Milla, P J (Gut, 1996)
BACKGROUND: Chronic idiopathic intestinal pseudo-obstruction (CIIP) presenting in infancy is a rare but serious condition of heterogeneous aetiology often with an uncertain outcome. AIM: To assess whether intestinal manometry in the first two years of life can help define a neuropathic or myopathic aetiology or clinical outcome, or both, in cases of infantile CIIP. SUBJECTS AND METHODS: 14 consecutive children who presented in the first year of life with CIIP were studied histologically and by small intestinal manometry. RESULTS: Five had a myopathic disorder, four were neuropathic, and five unclassified following histological investigation of full thickness intestinal biopsy specimens. Analysis of fasting phase III activity showed four patterns: (1) (n = 4) no detectable motor activity, (2) (n = 5) low amplitude phase III activity, (3) (n = 3) poorly formed phase III complexes of short duration, (4) (n = 2) well formed cyclical phase III activity with abnormal propagation. The seven children with low amplitude phase III: motility index (MI) < 10 KPa/min, all had a poor outcome (death or dependence on parenteral nutrition) after 1-10 years follow up, compared with two of seven of those with a MI > 10 KPa/min. Of the five with myopathic histology, four had a MI < 10 KPa/min. CONCLUSION: These results show that small intestinal manometry is useful not only as an aid in diagnosing the aetiology of CIIP presenting in infancy, but also in predicting outcome.